(untitled) (Bulletin KNOB, 2022)
In late 1895, in response to an ostensibly innocuous budget debate in the Lower House, a public war of words erupted over the prospective restoration and conversion of the Grafelijke Zalen (Counts’ Chambers) in the Binnenhof. Its desirability was not in dispute. However, in a matter of weeks, the discussion about which course to pursue and who should assume responsibility for the project escalated into a full-scale duel. On one side of the debate stood the Ministry of the Interior, led by the chief civil servant of the Department of Arts and Sciences (Kunsten en Wetenschappen or K&W), Victor de Stuers, and the architect Pierre Cuypers. Opposing them were the Ministry of Water, Trade and Industry (Waterstaat, for short) and the Society for the Advancement of Architecture (Maatschappij tot Bevordering der Bouwkunst). After De Stuers and Cuypers had implicitly claimed the project for the Ministry of the Interior, the Society registered a highly critical protest: it demanded that the Lower House leave responsibility for this ‘national treasure’ with the Ministry of Water, Trade & Industry and break with the fifteen-year-long approach to restorations dictated by K&W. The ‘stylistic purity’ demanded by De Stuers and Cuypers, based on their rather linear view of architectural history, left little scope for the Society’s somewhat more relativist approach, which combined restoration of a building’s artistic and historical values with the possibility of preserving multiple chronological layers. In the past De Stuers and Cuypers had nearly always managed, with the help of a few political intrigues, to impose their architectural vision, but on this occasion they were blocked by the Lower House. The Minister of Water, Trade & Industry set up a four-member restoration commission – his own government architects, D.E.C. Knuttel and C.H. Peters, plus C. Muyskens and F.J. Nieuwenhuis from the Society – and invited his colleague from the Ministry of the Interior to appoint a fifth member. It was not until eighteen months later that Cuypers was duly appointed to the position and the restoration commission could set to work. The normally assertive Cuypers appears to have exerted very little influence over the course pursued by the commission. Instead of his highly developed appreciation for the gothic style, it was the concrete building history research of Peters and Nieuwenhuis that underpinned the commission’s choices. De Stuers and Cuypers continued to wield influence, but their near total dominance of government policy was a thing of the past and after the completion of the restoration in 1905 there was gradually more scope for other views on heritage restoration ethics.